Makna Simbolik Appabbajikang Bunting Pada Prosesi Pernikahan Adat Makassar di Desa Pattallikang Kabupaten Gowa - Putri R, Dewi Kania; Hajrah; Asia M (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research is entitled The Symbolic Meaning of Appabbajikang bunting in the Makassar Traditional Wedding Procession in Pattallikang Village, Gowa Regency. This research aims to describe the icons, indices and symbols contained in the process of implementing appabbajikang bunting in Pattallikang village, Gowa Regency in terms of Charles Sanders Peirce's semiotic theory. This type of research is qualitative with a qualitative descriptive research design. The methods used in collecting data for this research were observation, interviews and documentation. The results of this research show that in the process of implementing the appabbajikang bunting tradition in Pattallikang village, Gowa Regency it has the meaning of (1) icons, namely tai bani and doek. (2) the meaning of the index, namely dupa, nipaasori lipak, and nisioi na sisioi kanrejawa. (3) the meaning of the symbols, namely jajjakkang, umba-umba, tai bani, doek, kanrejawa lapisik, lawarak kadea, kanrejawa sirikaya, songkolok palopok, jeknek inung, lekok kalomping, lipak. In general, the meaning contained in the tradition of the appabbajikang bunting procession in Pattallikang village, Gowa Regency is to unite the bride and groom, obtain abundant fortune, and have a prosperous household life.